Health care professionals' perspectives on the requirements facilitating the roll-out of kangaroo mother care in South Africa - Wilma ten Ham; Karin C.S. Minnie; Christa S.J.C. van der Walt (AOSIS, 2016)
Background: Using best evidence to inform practice is the cornerstone of quality patient care, and requires spread, uptake, implementation and roll-out of best practices. Kangaroo mother care (KMC) was used as a best practice which has been partly rolled-out in South Africa. In order for successful roll-out of best practices, it is important to understand what health professionals perceive as requirements for the rolling-out process. However, no published research was found on requirements for rolling-out a best practice in the South African context. Purpose of the research: To explore and describe the perspectives of health professionals on the requirements for the rolling-out process of KMC as a best practice in South Africa. Methodology: Twelve semi-structured individual interviews were conducted in 2012 with health professionals from various South African healthcare levels, involved in the implementation and the rolling-out process of kangaroo mother care. Content analysis were guided in terms of the four requirements for roll-out of best practices, identified in Edwards and Grinspun's Evidence Informed Model of Care. Results: The requirements for the successful rollout of best practices mentioned by the participants in this study concur with the requirements of Edwards and Grinspun: personal alignment and protocol/policy alignment with the best practice; a roll-out plan; leadership; and supporting and reinforcing structures such as: resources, communicating, education and development regarding the best practice, and the organisational structure. The requirements were identified at four different levels: individual level (e.g. the nurse and medical specialists), management level (of the hospital), provincial level and national level.